Algonquin materials, Frank G. Speck Papers - Speck, Frank G. (Frank Gouldsmith), 1881-1950; Bailey, Alfred Goldsworthy; Weitzner, Bella (1912)
Materials relating to both Algonquin and related Algonquian peoples, cultures, and languages. Includes Speck's notes on artifacts found near Lake Abitibi and in the Nipissing district; his Seven Islands field notes, including texts with interlinear translations, house data, names of animals, and a letter in French from Marie Louise Ambroise; abstracts of Speck's published works on the Rama-Chibcha of Nicaragua, River Desert Algonquins, Southern Ontario Indians, Maya, and others; sketches and comments on shoulder blade divination (scapulimancy), including notes on deer drives (including an undated note from A. Irving Hallowell) and the distribution of artifacts among Algonquin, Naskapi, and Mistassini peoples; two field notebooks containing (1) linguistic notes and informant and population data for Waswanipi, Abitibi, Temiskaming [Timiskaming], Nipissing, Algonquian and (2) Temiskaming ethnography, Wisiledjak (Wiskyjack) [Wisakedjak, a manitou] text (in English), Temagami ethnology and texts (in English), and one Iroquois legend; general information on birch-bark containers, including 37 photographs and 40 pages of notes relating to Algonquin, Cree, Ojibwe and Ktunaxa specimens, and a letter from Bella Weitzner; and a letter from A. G. Bailey sending Speck a copy of his book on Algonquians.